New Zealand : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, and Securities Regulation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper presents key findings of the Financial System Stability Assessment for New Zealand, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, and Securities Regulation. The assessment reveals that New Zealand has a profitable and well-functioning financial system, operating in a framework of well-developed financial markets. Short-term risks to stability appear low, given the favorable macroeconomic outlook, and sound and transparent financial policies. Stress tests for systemically important banks show resilience consistent with the sector's relatively high levels of capital and profits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet